KEHANDALAN ALKITAB MENJADI FONDASI BAGI PENGAJARAN TENTANG YESUS KRISTUS - Aprianus Ledrik Moimau (Phronesis: Jurnal Teologi dan Misi, 2020)
The Bible which is the source of Christian teaching has been doubted by saying that the Bible has been falsified and cannot be used as a basis in building Christian teachings, especially regarding the person of Jesus Christ. The gospels which are the primary source of Jesus Christ have been falsified and as such cannot be the basis for finding the real Jesus. Bible truth and reliability, especially the Gospels are questioned. If the Bible is relied upon in building knowledge and faith in Jesus Christ, what are the criteria in determining the reliability of the Bible? The purpose of this study is to find out whether the Bible has reliability that can be used as a standard in building Christian doctrines, especially regarding the person of Jesus Christ. In this study, a study was conducted on aspects of biblical bibliography, internal evidence tests and tests. external. Based on research conducted on the Bible, historical search, Bible data and from external evidence carried out by taking a test of historical truth, the Bible has a deepness in building Christian doctrines, specifically the Gospels have a depth in finding and believing in Jesus Christ stated in the Bible. The reliability of the Bible is proven and thus the person of Jesus Christ exposed by the Bible is true.